2018
DOI: 10.1002/ejic.201801012
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenacyclic Carbamoyl Complexes: Highly Efficient Catalysts for Organosilane Hydrolysis

Abstract: The ruthenacyclic carbamoyl complexes [RuX{2-NHC(O)C 5 H 3 NR}(CO) 2 (NCMe)] (R = H and Me; X = Br and SC 6 H 3o,o-Me 2 ) are excellent catalysts for the hydrolysis of organosilanes, particularly towards primary silanes, generating hydrogen [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…The X-ray crystal structural determination of 3b has been reported previously [28], and those for 3a, 3b", 4a, 4a', 4b", 4c" and 5 are reported here. The ORTEP plots illustrating the molecular structures of 3b", 4b" and 5 are given in Figure 2, and selected bond parameters together with a common atomic labelling scheme for all these complexes are collected in Table 1.…”
Section: Crystallographic Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The X-ray crystal structural determination of 3b has been reported previously [28], and those for 3a, 3b", 4a, 4a', 4b", 4c" and 5 are reported here. The ORTEP plots illustrating the molecular structures of 3b", 4b" and 5 are given in Figure 2, and selected bond parameters together with a common atomic labelling scheme for all these complexes are collected in Table 1.…”
Section: Crystallographic Discussionmentioning
confidence: 61%
“…Although a number of studies have shown that ruthenium complexes containing a four-membered metalla-heterocyclic ring are unexpectedly stable [28,29], the complex 2, which contains a chelating N,S-donor ligand [27], shows similar behaviour as 1 (Scheme 2). Thus, its reactions with one and two equivalents of PMe3 are instantaneous and give the mono-and di-adducts 3b" and 4b", respectively, via opening of the four-membered metalla-heterocyclic ring at the nitrogen atom; the analogous reaction with P(n-Bu)3, however, does require more forcing conditions (75 o C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9,10,11 We recently reported the synthesis and physical properties of metallacyclic carbamoyl complexes 1n as structural analogues of this cofactor for the group VIII triad, viz., iron, ruthenium and osmium (Figure 1b). 12,13,14 An interesting aspect of these complexes is that the 2mercaptopyridine ligand is hemilabile; it imparts stability to the complexes and yet is capable of decoordination at the pyridine-N. 12 This property makes the complexes potential catalysts and indeed, as we would like to report here, they are efficient catalysts for alkyne hydroxycarboxylation and electrochemical proton reduction.…”
Section: Introductionmentioning
confidence: 78%